(untitled) (Global Journal of Human-Social Science, 2012)
The study juxtaposed the imperativeness of psychological inventory in the execution of counseling programmes and presented the validity and reliability of the Crime Behaviouor Factor Battery, and its relevance in diagnosing crime intentions. It investigated the effectiveness of PISCO Creativity Thinking Tool in remediating criminal intentions among the unemployed graduates in Osun State, Nigeria, to foster societal security. 120 unemployed graduates were purposively selected on the basis of convenience, availability and simple randomization from Iwo and Ayedire Local Government in Osun State. Their ages range from 21-36 with a mean of 28.5. Sixty participants from Iwo Local Government formed the experimental group while sixty in Ayedire formed the control. The experimental group was exposed to training in PISCO creativity thinking tool for a period of six weeks, while the control group waited for its turn.